A glyoxylate-containing benzene derivative and butenolides from a marine algicolous fungus Aspergillus sp. SCSIO 41304. Issue 3 (1st February 2023) - Qi, Xin; Chen, Wei-Hao; Lin, Xiu-Ping; Liao, Sheng-Rong; Yang, Bin; Zhou, Xue-Feng; Liu, Yong-Hong; Wang, Jun-Feng; Li, Yong
Abstract: A new glyoxylate-containing benzene derivative, methyl 2-(4-hydroxy-3-(3′-methyl-2′-butenyl)phenyl)-2-oxoacetate (1 ), together with ten known compounds (2 –11 ), were isolated from the marine algicolous fungus, Aspergillus sp. SCSIO 41304. Their planar structures and absolute configurations were elucidated by detailed NMR, MS spectroscopic analysis and comparing with literature data. Compound 1 was isolated as a new fungal secondary metabolite, possessing a methyl glyoxylate moiety R-CO-CO-OCH3, which is rare in natural sources. All the isolated compounds (1 –11 ) were tested for their antibacterial and enzyme inhibitory activities against acetylcholinesterase (AChE) and pancreatic lipase (PL). Among these compounds, aspulvinone H (4 ) showed moderate inhibition against AChE and PL with IC50 values of 25.95 and 47.06 μ M, respectively. Further molecular docking simulation exhibited that compound 4 could well bind to the catalytic pockets of the AChE and PL. Graphical Abstract: UF0001